Diffused Pulmonary Uptake of Tc-99m Methylene Diphosphonate Bone Scan in Patient with Prostate Cancer without Blood Test and Correlative/Cross-Sectional Imaging Abnormalities: A Case Report - Imaniar, Junan; Suh, Minseok; Dewi, Ayu Rosemeilia; Tuti, Yustia (http://dharmais.co.id/, 2024)
Introduction: Bone scan using Tc-99m methylene diphosphonate (MDP) is a commonly used procedure for evaluating bone metastasis in cancer patients. Extra-osseous pulmonary uptake in bone scans is mostly an incidental finding and occurs in a multitude of disorders. Clinicians should be alert to any findings on clinical or complementary diagnostic tools. We presented a case of prostate cancer male patients who demonstrated diffuse pulmonary uptake on Tc-99m MDP bone scan without any blood test and correlative/cross-sectional imaging abnormality Case Presentation: An 80-year-old male with adenocarcinoma of the prostate with a Gleason score of 6 (3+3). The PSA level was 0.009. The patient had a history of recurrent atrial fibrillation (AF), postural dizziness, HTN, Gout, and chronic renal failure, but all of these comorbidities were under control. The patient underwent a bone scan to annually check for the presence of bone metastases. Three hours after administering 740 MBq Tc-99m MDP intravenously. The reports didn’t show any increased uptake that would indicate metastases in the bones. Instead, diffuse bilateral pulmonary uptake and a mild increase in cardiac uptake were present. On the same day, a computed tomography (CT) scan of the thorax revealed 3 micro-nodules in the right upper lung that were described as benign lesions, and a chest X-ray confirmed normal results. The patient’s laboratory results were within normal range, and there were no clinical lung symptoms or complaints. Considering the patient history of persistent AF, chronic renal failure, and a complaint of postural dizziness, the bone scan finding may indicate involvement of amyloidosis. The relationship between amyloidosis and cancer was also widely noted. Conclusions: Tc-99m MDP may play a role in evaluating amyloidosis involvement in an uncommon place such as the lungs. Future research should focus on analyzing diagnostic options in the patient’s condition in this situation. Keywords: cancer, diffused pulmonary uptake, amyloidosis, bone scan